2002
DOI: 10.1124/jpet.102.036962
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of theN-Methyl-d-Aspartate Receptor by Calpain in Situ

Abstract: N-Methyl-D-aspartate (NMDA) receptors are calcium-permeable glutamate receptors that play putative roles in learning, memory, and excitotoxicity. NMDA receptor-mediated calcium entry can activate the calcium-dependent protease calpain, leading to substrate degradation. The major NMDA receptor 2 (NR2) subunits of the receptor are in vitro substrates for calpain at selected sites in the C-terminal region. In the present study, we assessed the ability of calpain-mediated proteolysis to modulate the NR1a/2A subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…Calpain activation results in cleavage of the C-terminal tail (around amino acid 1030) of the NR2B subunit of NMDARs (Bi et al, 1998a;Guttmann et al, 2001Guttmann et al, , 2002Simpkins et al, 2003). We hypothesized that the elevated calpain activity levels we found in YAC128 striatal neurons would be associated with an increased proportion of calpain-cleaved NR2B.…”
Section: Nr2b Fragment Produced By Calpain Cleavage Is Increased In Ymentioning
confidence: 91%
“…Calpain activation results in cleavage of the C-terminal tail (around amino acid 1030) of the NR2B subunit of NMDARs (Bi et al, 1998a;Guttmann et al, 2001Guttmann et al, , 2002Simpkins et al, 2003). We hypothesized that the elevated calpain activity levels we found in YAC128 striatal neurons would be associated with an increased proportion of calpain-cleaved NR2B.…”
Section: Nr2b Fragment Produced By Calpain Cleavage Is Increased In Ymentioning
confidence: 91%
“…It seems that protein phosphatase 1-mediated KCC2 dephosphorylation cannot fully explain the profound reduction in the KCC2 protein level in the spinal cord by nerve injury. It has been shown that NR2 subunits are substrates of calpain and that activation of NMDARs can activate calpain, which in turn down-regulates the NMDAR function (57,58). However, PSD-95 clustering and direct association of NR2 and PSD-95 may prevent calpain cleavage of NMDARs (59).…”
Section: Discussionmentioning
confidence: 99%
“…Classic NMDA-type glutamate receptors are heteromeric proteins composed of two NR1 subunits and two NR2 subunits, selected from subtypes NR2A, NR2B, NR2C, and NR2D. Of these, NR2A, -2B, and -2C are known to undergo Cterminal proteolysis by calpain in vitro (Guttmann et al, 2002), a truncation that does not appear to prevent any aspects of receptor function. However, only the NR2B subunit has been (Xu et al, 2007) shown to be cleaved by calpain in mature neurons (Dong et al, 2006).…”
Section: Plasma Membrane and Synapsementioning
confidence: 99%